2019
DOI: 10.3892/etm.2019.7438
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plasma miR‑142‑5p promotes the progression of intrahepatic cholangiocarcinoma via targeting PTEN

Abstract: The aim of the present study was to evaluate the expression and specific role of microRNA (miR)-142-5p in the progression of intrahepatic cholangiocarcinoma (ICC). Reverse transcription-quantitative polymerase chain reaction was performed to evaluate miR-142-5p expression in patients with ICC and healthy control subjects. The results revealed that plasma miR-142-5p was significantly increased in patients with ICC compared with the control group. Furthermore, miR-142-5p was also increased in ICC tissues compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…dysregulated expression or function of miRNAs has been demonstrated in a series of malignancies, including ccA (25). For example, miR-142-5p was shown to decrease the expression of phosphatase and tensin homolog and promote the progression of ccA (26). It was demonstrated that miR-329 can suppress the expression of pituitary tumor-transforming 1, inactivates the mitogen-activated protein kinase/extracellular signal-regulated kinase signaling pathway and has the potential to suppress ccA cell proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…dysregulated expression or function of miRNAs has been demonstrated in a series of malignancies, including ccA (25). For example, miR-142-5p was shown to decrease the expression of phosphatase and tensin homolog and promote the progression of ccA (26). It was demonstrated that miR-329 can suppress the expression of pituitary tumor-transforming 1, inactivates the mitogen-activated protein kinase/extracellular signal-regulated kinase signaling pathway and has the potential to suppress ccA cell proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…The included articles were published between 2011 and 2020. Fifteen and five articles were published in English [ 7–20 , 23 ] and Chinese [ 21,22 , 24–26 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Five and fifteen articles detected the expression of miR-142 in blood and tissues, respectively. A total of 12 solid tumors were included, namely HCC [ 8 , 10 ], CRC [ 9 ], NSCLC [ 11 , 24 ], CC [ 12 , 15 , 21 , 26 ], NPC [ 13 ], EC [ 18 ], ESCC [ 14 , 22 ], RCC [ 16 ], glioma [ 17 ], ICC [ 7 ], GC [19,20,], melanoma [ 23 ] and OSCC [ 25 ]. The average NOS score of the included articles was 6.40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports on the relationship between ICC tumor cells and miRNAs. Wei et al 23 reported that miR‐142‐5p promotes ICC tumor cells by targeting PTEN. Wu et al 24 also reported that miR‐424‐5p suppresses ICC tumor cells via ARK5.…”
Section: Discussionmentioning
confidence: 99%